Examining the technical feasibility of prostate cancer molecular imaging by transrectal photoacoustic tomography with transurethral illumination. Issue 4 (February 2020) - Zhang, Haonan; Huang, Shengsong; Chen, Yingna; Xie, Weiya; Zhang, Mengjiao; Pan, Jing; Sato, Naoto; Wang, Xueding; Wu, Denglong; Cheng, Qian
To pave the road toward clinical application of photoacoustic imaging in prostate cancer (PCa) diagnosis, we studied the technical feasibility and performance of transrectal photoacoustic (PA) imaging in mapping the indocyanine green (ICG) contrast agent, which is approved by FDA, in entire prostates by using light illumination via the urethral track. Experiments were conducted on a clinically relevant ex vivo model involving whole human prostates harvested from radical prostatectomy. The light source placed in the urethral track was an array of light emitting diodes (LEDs), illuminating the prostate with a delivered light power on the urethral wall within the safety limit. A dual-modality imaging system acquired PA and ultrasound (US) images simultaneously in the same way as in transrectal ultrasound (TRUS), with the US imaging presenting the tissue structure and PA imaging detecting the ICG solution. The imaging results demonstrated that tubes containing ICG solution at different concentrations can be detected at different positions in the prostate within a 2 cm range around from the urethral wall. Considering the sizes of regular human prostates, the proposed transurethral illumination in combination with transrectal US detection can facilitate PA molecular imaging over the entire prostate in a non-invasive manner, which makes it possible to further improve the PCa diagnosing efficiency with better molecular sensitivity and resulted better biopsy accuracy and much reduced pain for patients. Impact statement: Differentiating cancerous tissues from healthy ones is critical in the diagnosis of prostate cancer (PCa). However, due to the low sensitivity of ultrasound (US) imaging to cancerous tissues, transrectal ultrasound (TRUS) guided biopsies, current standard procedure for diagnosing PCa, suffer from low core yield, leading to under-sampling and under-grading of clinically significant tumors. Via the experiment on the ex vivo human prostates, we evaluated the translational potential of photoacoustic imaging (PAI) based on a safe light emitting diodes (LED) source for detecting the molecular information in deep human prostate. We showed that transurethral light illumination in combination with transrectal US detection can facilitate PA molecular imaging over an entire human prostate in a non-invasive manner. The success of this study in the clinically relevant ex vivo human prostate model suggested a new strategy for PA and US combined imaging and detection of PCa.